The Impact of SAP Business Technology Platform (BTP) on Financial Data Analytics and Reporting - Rahul Bhatia (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper examines how the SAP Business Technology Platform (BTP) has impacted financial data analytics and reporting. The article then addresses how BTP successfully applies real-time analytics, predictive modelling, Artificial Intelligence (AI), and Machine Learning to enhance decision-making and reporting efficiency without trade-offs. SAP BTP brings data silos out of ERP systems, and by consolidating data into a single system, the accuracy, speed, and consistency of reporting improve. The article points out how SAP Analytics Cloud (SAC) is an interactive dashboard and analytics platform that allows real-time insights. The key result summarizes substantial gains in report generation time, cash flow management, and supply chain optimization. However, the study also acknowledges that the implementation complexity, data quality, and security concerns constrain its potential. Future analysis seeks to address these limitations and advance the use of new technologies, such as Blockchain and Quantum Computing, to explore more innovative ways of exploring financial data analysis.